Climate change and hydrometeorological influence on water resources a study on 2014 water rationing in Selangor, Malaysia - Ithnin Hamirdin, Baharom Azmi Ahmad, (N/A, 2014)
Climate change and hydrometeorological influence on water resources a study on 2014 water rationing in Selangor, Malaysia by Ithnin Hamirdin, Baharom Azmi Ahmad,